Parentification of the Eldest Sibling in the Care of a Sibling with Special Needs and Multiple Disabilities (Cerebral Palsy, Autism and Epilepsy) - Anwar, Nurmelisa; Oktavia, Citrawanti (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
This study examines the phenomenon of parentification experienced by a 20-year-old elder sibling who cares for a younger sibling with dual special needs (Cerebral Palsy, Autism Spectrum Disorder, and Epilepsy) aged 12 years. Parentification occurs after the subject loses their father at age 16, leading them to take on significant caregiving and family responsibilities. The research employs a case study approach with a qualitative method, involving in-depth interviews, participatory observation, and supporting documentation. The findings indicate that the subject plays a significant emotional and instrumental role, including caring for the sibling, assisting with household chores, and contributing financially while continuing their education. This role impacts their personal life, especially in managing time and prioritizing between college, work, and caregiving. Despite the heavy burden, the subject demonstrates maturity, independence, and a high sense of responsibility. The study emphasizes the importance of social support and appropriate interventions to assist children and adolescents experiencing parentification, particularly in families with children with special needs. These findings are expected to serve as a basis for developing family support programs and enhancing psychosocial well-being.